2013
DOI: 10.1038/srep01867
|View full text |Cite
|
Sign up to set email alerts
|

IRGM1 regulates oxidized LDL uptake by macrophage via actin-dependent receptor internalization during atherosclerosis

Abstract: Macrophage derived foam cells are actively involved in the initial phase of atherosclerosis. Uptake of modified lipoprotein such as oxidized LDL (oxLDL) is a critical step for foam cell formation. CD36 is the major receptor mediating oxLDL uptake by macrophage. However, the molecular mechanism underlying CD36 mediated oxLDL uptake remains unclear. Here we reported that IRGM1 (IRGM in human), a member of immunity-related small GTPase family, is essential for the actin-dependent CD36 mediated oxLDL uptake by mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 21 publications
2
22
0
1
Order By: Relevance
“…Liu et al33 demonstrated a non-volatile switching of Verwey transition of Fe 3 O 4 with the 71° ferroelastic domain wall switching. The unique ferroelastic pathway was achieved by sweeping the electric field near the electric coercive field of PMN-PT.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al33 demonstrated a non-volatile switching of Verwey transition of Fe 3 O 4 with the 71° ferroelastic domain wall switching. The unique ferroelastic pathway was achieved by sweeping the electric field near the electric coercive field of PMN-PT.…”
Section: Resultsmentioning
confidence: 99%
“…The reduced citrate availability would probably have the effect of decreasing fatty acid synthesis as well as promoting glycolysis by reducing the inhibitory effect of citrate on phosphofructokinase (85). It is plausible that Irgm1 could play a direct role in lipid homeostasis, because it is a dynamin-like GTPase that associates with specific intracellular membrane compartments, including the Golgi, where it may alter membrane trafficking (11,12,21,25,52,78,87). Additionally, IRGM proteins have been reported to play roles in lipid droplet maintenance (27,78,88).…”
Section: Discussionmentioning
confidence: 99%
“…According to these observations, it has been demonstrated that there is an increased expression of IRGM by macrophages around the atherosclerotic plaque, suggesting a possible role of IRGM-mediated autophagy in cardiovascular disease. 9,10…”
mentioning
confidence: 99%